2015
DOI: 10.1002/xrs.2636
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties and chemical bonds in double metal cyanide catalysts

Abstract: Double metal cyanide (DMC) catalysts are commonly applied at industrial ring-opening polymerization of the epoxides, being the initial stage of the polyurethanes manufacturing route. This group of catalysts is frequently used in industry, but the knowledge on the molecular nature of their high activity and selectivity is limited to some phenomenological hypotheses based on overall chemical premises. To shine some light on the relation between structural and chemical properties of DMC catalysts and their activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Die Verwendung von DMC‐Katalysatoren für die Homopolymerisation von Epoxiden wie auch für die Copolymerisation von CO 2 mit Epoxiden und anderen Comonomeren, wie cyclischen Anhydriden und Lactonen, ist bekannt . Die katalytisch aktiven Metallzentren sind tetraedrisch koordinierte Zn‐Atome mit benachbarten Cl‐Atomen, wie durch Röntgenfeinstrukturanalyse gezeigt wurde . Die Möglichkeit, unterschiedliche Substrate mit DMC‐Katalysatoren zu polymerisieren, veranlasste uns, funktionelle Comonomere (MA und AGE) in einer Mehrkomponentenpolymerisation einzusetzen.…”
Section: Methodsunclassified
“…Die Verwendung von DMC‐Katalysatoren für die Homopolymerisation von Epoxiden wie auch für die Copolymerisation von CO 2 mit Epoxiden und anderen Comonomeren, wie cyclischen Anhydriden und Lactonen, ist bekannt . Die katalytisch aktiven Metallzentren sind tetraedrisch koordinierte Zn‐Atome mit benachbarten Cl‐Atomen, wie durch Röntgenfeinstrukturanalyse gezeigt wurde . Die Möglichkeit, unterschiedliche Substrate mit DMC‐Katalysatoren zu polymerisieren, veranlasste uns, funktionelle Comonomere (MA und AGE) in einer Mehrkomponentenpolymerisation einzusetzen.…”
Section: Methodsunclassified
“…It is found that the induction time is not influenced by the presence of TEA or DDA. Propoxylation reactions mediated by DMC catalysts [71][72][73] generally feature an induction period as substrates from synthesis bind to the catalyst surface, which prevent PO coordination and therefore catalytic activity [93,94]. The catalyst activation is commonly carried out by addition of a small amount of epoxide to a DMC catalyst suspended in a starter (mainly diols as CTA) of low molecular weight [95][96][97][98], such as here in form of Lupranol1200.…”
Section: Amines As Cocatalyst/conucleophilementioning
confidence: 99%
“…Proposed reaction routes in double metal cyanide (DMC)-mediated propoxylation of alcohols, external attack of CTA ROH and proton transfer (a) and "insertion" of PO in a zinc alkoxide bond after (reversible) RO − dissociation (b). Formulated in the essence of single zinc site catalysis for simplicity, more interactions will be present; structures would be derived from the 001/100 plane of DMC crystals [69][70][71].…”
Section: Introductionmentioning
confidence: 99%
“…To accurately model the luminescence behavior of K 3 10 ]. This anionic model was selected based on its ground-state structural agreement with the crystal structure, as shown in Figure 5 and Table S2.…”
Section: Molecular Modelingmentioning
confidence: 99%